Composite phase change material and preparation method thereof, polycarbonate composite material and preparation method thereof
Patent Information
- Application Number
- CN202510563055.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本申请的主要目的在于提供一种复合相变材料及其制备方法、聚碳酸酯复合材料及其制备方法,以解决现有技术中聚碳酸酯材料耐烧穿性能差的问题
[0032]应用本申请的技术方案,选用多孔玻璃微珠和熔盐作为复合相变材料,一方面,在聚碳酸酯复合材料遇火时,盐可以发生相变,由固态转变为液态,这个过程会吸收大量的热能,有效减缓材料表面温度的急剧升高,从而为材料提供额外的热防护,延长达到燃点的时间。另一方面,多孔玻璃微珠在高温下开始熔化,形成致密的玻璃膜,这些玻璃膜能够在外壳表面形成一个物理屏障,隔绝氧气和火焰,阻止进一步的氧化和燃烧反应,同时,形成的玻璃能够增强聚碳酸酯材料炭化后的机械强度,防止结构坍塌,进而改善聚碳酸酯复合材料的耐烧穿性能。除此之外,部分盐位于多孔玻璃微珠的孔内,有助于改善多孔玻璃微珠熔化后形成的玻璃膜的包覆效果,还能保护盐,避免其泄露;通过控制多孔玻璃微珠和盐的质量比可以进一步优化复合相变材料的热稳定性和阻燃效果,提升聚碳酸酯复合材料的耐烧穿性能。
Smart Images

Figure BDA0005385597830000131 
Figure BDA0005385597830000141
Abstract
Description
Technical Field
[0001] This application relates to the field of fireproof shell material technology, specifically to a composite phase change material and its preparation method, and a polycarbonate composite material and its preparation method. Background Technology
[0002] Polycarbonate (PC) is a thermoplastic polymer. As one of the five major general-purpose engineering plastics, it has excellent transparency, impact toughness, gloss, and dimensional stability. It also has a high limiting oxygen index and can be processed in various ways. It is widely used in consumer electronics, electrical appliances, automobiles, aerospace and other fields.
[0003] However, with technological advancements and increasingly stringent safety standards, especially the introduction of the GB4943.1-2022 standard, more stringent requirements have been placed on the burn-through resistance of fire-resistant casing materials. While traditional polycarbonate materials possess excellent electrical insulation, heat resistance, and impact resistance, their effectiveness in fire-resistant applications is limited by melting deformation and collapse at high temperatures. This is particularly true in porous consumer electronics products such as mobile phones, laptops, televisions, and printers. Traditional PC fire-resistant casings often burn through within 20-30 seconds when exposed to flames, posing a significant threat to users' lives and property.
[0004] The root of the problem lies in the thermal stability limitations of polycarbonate (PC). It easily melts at high temperatures, causing the material structure to collapse and resulting in the loss of its physical and mechanical properties, leading to burn-through of the casing. Furthermore, flame retardants in PC materials often only provide initial protection during combustion, failing to sustainably suppress flame spread at high temperatures, let alone prevent burn-through. Therefore, finding a new composite material that can maintain structural stability and improve burn-through resistance at high temperatures has become a crucial research direction for fire-resistant casing materials. This requires not only materials that can resist flame attack for a short time but also that are resistant to burn-through over a longer period to meet higher safety standards. Faced with this challenge, the industry urgently needs an innovative solution to enhance the burn-through resistance of polycarbonate materials under high-temperature conditions, ensuring the safety of electronic devices in accidental fires. Summary of the Invention
[0005] The main objective of this application is to provide a composite phase change material and its preparation method, and a polycarbonate composite material and its preparation method, so as to solve the problem of poor burn-through resistance of polycarbonate materials in the prior art.
[0006] To achieve the above objectives, according to a first aspect of this application, a composite phase change material is provided, comprising porous glass microspheres and salt, wherein at least a portion of the salt is located within the pores of the porous glass microspheres; the mass ratio of the porous glass microspheres to the salt is (80-90):(10-20), and the salt forms molten salt after melting.
[0007] Furthermore, the salt includes sodium nitrate and potassium nitrate, and the mass ratio of sodium nitrate to potassium nitrate is (4-6):(4-6).
[0008] Furthermore, the average particle size of the salt is 1 μm to 5 μm.
[0009] Furthermore, the average particle size of the porous glass microspheres is 50 μm to 100 μm.
[0010] Furthermore, the melting temperature of the porous glass microspheres is 550℃~650℃.
[0011] Furthermore, the average pore size of the porous glass microspheres is 1 μm to 5 μm.
[0012] Furthermore, the porosity of the porous glass microspheres is 20%–50%.
[0013] According to a second aspect of this application, a method for preparing the composite phase change material of the first aspect of this application is provided, comprising the following steps:
[0014] S1, heat the salt to 350℃~400℃, then add porous glass microspheres to obtain a mixture;
[0015] S2, the mixture was subjected to heat preservation and pressure treatment at 300MPa~500MPa and 350℃~400℃ to obtain a composite phase change material;
[0016] The mass ratio of porous glass microspheres to salt is (80-90):(10-20), and the salt melts to form molten salt.
[0017] Furthermore, in S2, after the heat preservation and pressure treatment, grinding, cleaning, and drying are also included; after drying, a composite phase change material is obtained.
[0018] Furthermore, the salt includes sodium nitrate and potassium nitrate, and the mass ratio of sodium nitrate to potassium nitrate is (4-6):(4-6).
[0019] According to a third aspect of this application, a polycarbonate composite material is provided, comprising the following components in parts by weight: 89-94.7 parts polycarbonate, 0.5-1.5 parts flame retardant, 1-2 parts composite phase change material, 3-5 parts toughening agent, 0.2-2 parts antioxidant, and 0.1-1 parts lubricant.
[0020] Furthermore, the melt flow rate of polycarbonate measured at 300°C and 1.2 kg was 8 g / 10 min to 20 g / 10 min.
[0021] Furthermore, the number average molecular weight of polycarbonate is 24,000 g / mol to 30,000 g / mol.
[0022] Furthermore, the flame retardant is a sulfonate flame retardant.
[0023] Furthermore, the toughening agent is at least one of methyl methacrylate-butadiene-styrene copolymer, methyl methacrylate-organosilicon-acrylate copolymer, ethylene-1-octene copolymer, and ethylene-acrylic acid-glycidyl methacrylate copolymer.
[0024] Furthermore, the antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants.
[0025] Furthermore, the lubricant is at least one of silicone powder, pentaerythritol stearate, and stearamide.
[0026] According to a fourth aspect of this application, a method for preparing the polycarbonate composite material of the third aspect of this application is provided, comprising the following steps:
[0027] S1, mix polycarbonate, flame retardant, composite phase change material, toughening agent, antioxidant and lubricant to obtain a mixture;
[0028] S2, the mixture is added to an extruder for melting, extrusion and granulation to obtain a polycarbonate composite material.
[0029] Furthermore, in S1, mixing takes place inside a high-speed mixer.
[0030] Furthermore, in S2, the extruder is a twin-screw extruder.
[0031] Furthermore, in S2, the process parameters of the extruder are as follows: Zone 1 temperature 240℃~245℃, Zone 2 temperature 250℃~255℃, Zone 3 temperature 260℃~265℃, Zone 4 temperature 270℃~275℃, Zone 5 temperature 270℃~275℃, Zone 6 temperature 270℃~275℃, Zone 7 temperature 270℃~275℃, Zone 8 temperature 270℃~275℃, Zone 9 temperature 275℃~280℃, and die head temperature 285℃~290℃. The speed of the extruder is 300r / min~500r / min.
[0032] Applying the technical solution of this application, porous glass microspheres and molten salt are selected as composite phase change materials. On the one hand, when polycarbonate composites are exposed to fire, the salt can undergo a phase change, transforming from a solid to a liquid state. This process absorbs a large amount of heat energy, effectively slowing down the rapid rise in the surface temperature of the material, thereby providing additional thermal protection and extending the time to reach the ignition point. On the other hand, the porous glass microspheres begin to melt at high temperatures, forming a dense glass film. These glass films can form a physical barrier on the outer shell surface, isolating oxygen and flames, preventing further oxidation and combustion reactions. At the same time, the formed glass can enhance the mechanical strength of the polycarbonate material after carbonization, preventing structural collapse and thus improving the burn-through resistance of the polycarbonate composite. In addition, some salt is located within the pores of the porous glass microspheres, which helps improve the coating effect of the glass film formed after the porous glass microspheres melt, and also protects the salt from leakage. By controlling the mass ratio of porous glass microspheres to salt, the thermal stability and flame retardant effect of the composite phase change material can be further optimized, improving the burn-through resistance of the polycarbonate composite. Detailed Implementation
[0033] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0034] As described in the background section of this application, existing technologies suffer from insufficient burn-through resistance of polycarbonate composite materials. To address this technical problem, in a typical embodiment of this application, a composite phase change material is provided, comprising porous glass microspheres and salt, with at least a portion of the salt located within the pores of the porous glass microspheres; wherein the mass ratio of the porous glass microspheres to the salt is (80-90):(10-20), and the salt forms molten salt after melting.
[0035] In this embodiment, the salt transforms from a solid to a liquid state during a fire. This transformation process involves the absorption of a large amount of heat, which effectively reduces the rate of temperature rise on the material surface, providing additional thermal protection and significantly improving the heat resistance of the composite material. The porous glass microspheres melt under high-temperature conditions, forming a glass film. This film not only isolates oxygen and flames, preventing further oxidation and combustion reactions, but also forms an additional physical barrier on the material surface, effectively slowing the flame penetration rate and significantly enhancing the flame retardancy and burn-through resistance of the polycarbonate composite material. Controlling at least some of the salt to be located within the pores of the porous glass microspheres helps form a uniform and dense glass film on the surface of the polycarbonate material, enhancing its burn-through resistance and preventing salt leakage. Controlling the mass ratio of porous glass microspheres to salt to (80–90): (10–20) balances flame retardancy and burn-through resistance, enabling the polycarbonate composite material to better protect internal electronic equipment in the face of fire, meeting the requirements of standards such as GB4943.1-2022.
[0036] In some embodiments, the salt comprises sodium nitrate and potassium nitrate, and the mass ratio of sodium nitrate to potassium nitrate is (4-6):(4-6).
[0037] The aforementioned salts have low phase transition temperatures, allowing them to preferentially undergo phase transitions and absorb heat during a fire. Furthermore, the binary molten salt composed of sodium nitrate and potassium nitrate decomposes at high temperatures, producing gases such as NO2. The release of these gases dilutes the oxygen concentration in the combustion zone, inhibiting flame spread. Maintaining a mass ratio of sodium nitrate to potassium nitrate of (4–6):(4–6) facilitates the formation of a stable molten salt system within the composite material. This ensures rapid heat absorption in the initial stages of a fire while maintaining the fluidity of the molten salt at high temperatures, allowing it to distribute evenly within and around the porous glass microspheres, thus improving flame retardant efficiency.
[0038] In some embodiments, the average particle size of the salt is 1 μm to 5 μm.
[0039] Controlling the average particle size of the salt within the aforementioned range helps to increase its heat absorption rate, enabling it to rapidly reduce the surface temperature of the material during phase change and delay the thermal decomposition of polycarbonate, thereby effectively improving the flame retardant properties and burn-through resistance of the material. Furthermore, controlling the salt particle size within this range helps to ensure a more uniform distribution of the salt within the pores of the porous glass microspheres and in the matrix of the composite material. Uniformly dispersed salt ensures effective thermal protection and flame retardancy throughout the material, preventing a decrease in burn-through resistance due to uneven local salt distribution.
[0040] In some embodiments, the average particle size of the porous glass microspheres is 50 μm to 100 μm.
[0041] Controlling the average pore size of porous glass microspheres within the aforementioned range provides ample pore space within the composite material. This facilitates the absorption of significant heat by the salt at high temperatures and its rapid release upon cooling, enhancing the thermal protection capability of the polycarbonate composite and extending its burn-through resistance time. Furthermore, controlling the average particle size within this range promotes the rapid formation of a uniform glass film on the polycarbonate surface, improving the optimal air barrier effect. Additionally, the glass film formed after melting of the porous glass microspheres possesses superior mechanical strength, providing additional support for the carbonized layer of the polycarbonate and preventing softening and collapse at high temperatures. This significantly improves the structural stability of the composite material under combustion conditions and enhances its burn-through resistance.
[0042] In some embodiments, the average pore size of the porous glass microspheres is 1 μm to 5 μm; the porosity of the porous glass microspheres is 20% to 50%.
[0043] Controlling the average pore size of porous glass microspheres helps to increase the salt loading, providing more efficient heat absorption and flame retardancy for polycarbonate composites, which is crucial for improving the burn-through resistance of polycarbonate composites. Furthermore, under high-temperature conditions, the flame-retardant gases generated by the decomposition of molten salt need to be released from the pores. Controlling the average pore size within the aforementioned range ensures rapid gas release while preventing excessively rapid gas release from causing internal pressure imbalances that could affect the material's structural stability and flame-retardant effect. Controlling the porosity of the porous glass microspheres within the aforementioned range also facilitates molten salt storage, providing stronger heat absorption capacity at high temperatures. Additionally, increased porosity increases the specific surface area of the material, promoting the rapid formation of a dense glass film and improving the burn-through resistance of polycarbonate composites.
[0044] In some embodiments, the melting temperature of the porous glass microspheres is 550°C to 650°C.
[0045] Controlling the melting temperature of porous glass microspheres within the aforementioned range allows them to begin melting earlier in a fire environment, forming a dense glass film. This film provides protection before the fire reaches its maximum destructive power, effectively isolating heat and oxygen and slowing down the thermal decomposition rate of polycarbonate. Furthermore, the glass film formed within this melting temperature range exhibits good thermal stability and a certain degree of mechanical strength, significantly contributing to improving the burn-through resistance of polycarbonate composites.
[0046] In some embodiments, the porous glass microspheres are porous hollow glass microspheres.
[0047] Porous hollow glass microspheres have a low density, which helps to reduce the overall weight of polycarbonate composites. At the same time, due to their hollow nature, they help to reduce friction with other components during processing, improve material flowability, reduce processing energy consumption, and increase production efficiency.
[0048] Specifically, but not limitingly, the porous glass microspheres are at least one of SiO2·P2O5-based porous glass microspheres, borosilicate glass microspheres, silica glass microspheres, and alumina glass microspheres. All of the above porous glass microspheres can melt rapidly at high temperatures to form a dense glass film, which can effectively improve the burn-through resistance of polycarbonate composite materials.
[0049] In another typical embodiment of this application, a method for preparing the composite phase change material described in the above embodiments is provided, which includes the following steps:
[0050] S1, heat the nitrate to 350℃~400℃, then add porous glass microspheres to obtain a mixture;
[0051] S2, the mixture was subjected to heat preservation and pressure treatment at 300MPa~500MPa and 350℃~400℃ to obtain a composite phase change material;
[0052] The mass ratio of porous glass microspheres to nitrate is (80-90):(10-20).
[0053] The above method is relatively simple. By controlling the processing pressure and temperature, molten salt can enter the pores of porous glass microspheres and be uniformly distributed within them, forming a stable composite structure. In fire or high-temperature environments, the composite phase change material can better maintain its structural integrity, preventing premature leakage of the internal molten salt. Molten salt and porous glass microspheres can synergistically improve the heat absorption efficiency of polycarbonate composites, delay the thermal decomposition and combustion process of the polycarbonate matrix, and significantly enhance the burn-through resistance of polycarbonate composites.
[0054] In some embodiments, after the heat preservation and pressure treatment in step S2, grinding, cleaning, and drying steps are also included; after drying, a composite phase change material is obtained.
[0055] Grinding helps improve the dispersibility of the composite phase change material in polycarbonate. Cleaning includes washing with alkaline solutions such as potassium hydroxide and rinsing with water until neutral; these methods can remove impurities and oil from the composite phase change material. Drying is completed by holding at 80℃~120℃ for 5h~30h.
[0056] In another typical embodiment of this application, a polycarbonate composite material is provided, comprising the following components in parts by weight: 89-94.7 parts polycarbonate, 0.5-1.5 parts flame retardant, 1-2 parts composite phase change material, 3-5 parts toughening agent, 0.2-2 parts antioxidant, and 0.1-1 parts lubricant.
[0057] Flame retardants and composite phase change materials have a synergistic effect. By controlling their weight proportions within the aforementioned range, the flame retardant can promote polycarbonate carbonization in the early stages of combustion, forming a char layer to isolate oxygen. Meanwhile, the porous glass microspheres and molten salt in the composite phase change material, through endothermic phase change and the formation of a dense glass film, further enhance burn-through resistance and extend the material's survival time under flame. Adding an appropriate amount of toughening agent allows the polycarbonate composite material to maintain high flame retardancy while also retaining good mechanical strength and toughness. The addition of toughening agent significantly improves the brittleness of polycarbonate, enhances structural stability under high temperature or impact conditions, and, together with the porous glass microspheres in the composite phase change material, ensures that the material is not prone to brittle fracture and collapse under fire conditions. Adding an appropriate amount of antioxidant can effectively inhibit the performance degradation of polycarbonate caused by oxidation during long-term use, extending the service life of the polycarbonate composite material. The addition of lubricant reduces friction between polycarbonate molecules, improves the processing performance of the polycarbonate composite material, and helps to improve the uniformity of the polycarbonate composite material.
[0058] In some embodiments, the melt flow rate of polycarbonate measured at 300°C and 1.2 kg is 8 g / 10 min to 20 g / 10 min.
[0059] Controlling the melt flow rate of polycarbonate composites within the aforementioned range results in excellent flow properties. This means that the material can flow more smoothly during melt extrusion and injection molding, improving processing efficiency, reducing energy consumption and equipment wear. It also facilitates the uniform dispersion of other components in the composite (such as composite phase change materials, flame retardants, and toughening agents), improving product quality consistency. Furthermore, an appropriate melt flow rate helps form a more uniform microstructure in the composite, thereby optimizing its mechanical properties and extending the burn-through resistance time of the polycarbonate composite. Additionally, the melt flow rate of polycarbonate also affects the dispersion quality and reaction efficiency of flame retardants and composite phase change materials, ensuring consistent flame retardant effects across different parts of the polycarbonate composite, improving the utilization efficiency of composite phase change materials and flame retardants, and enhancing overall flame retardant performance.
[0060] In some embodiments, the number-average molecular weight of the polycarbonate is 24,000 g / mol to 30,000 g / mol.
[0061] Controlling the number-average molecular weight of polycarbonate within the aforementioned range helps to give polycarbonate composites high impact strength and toughness, while also providing good processing flowability. Simultaneously, within this range, the strong intermolecular forces improve the thermal stability of the polycarbonate composite. Under high-temperature or fire conditions, the thermal decomposition rate of the polycarbonate composite decreases, contributing to improved burn-through resistance and flame retardant properties.
[0062] In some embodiments, the flame retardant is a sulfonate flame retardant, specifically, but not limited to, potassium perfluorobutyl sulfonate, potassium diphenyl sulfonate, and sodium 2,4,5-trichlorobenzene sulfonate.
[0063] Sulfonate flame retardants decompose at high temperatures, releasing water vapor. This water vapor absorbs a significant amount of heat, lowering the temperature of the combustion zone and thus slowing or stopping the combustion process. Furthermore, sulfonate flame retardants can form a dense char layer on the surface of polycarbonate composites, providing heat insulation and oxygen barrier properties, thereby inhibiting the spread of combustion. In addition, sulfonate flame retardants can effectively capture free radicals generated during combustion, reducing the combustion rate. Moreover, sulfonate flame retardants can synergistically enhance the flame-retardant effect when combined with composite phase change materials.
[0064] In some embodiments, the toughening agent is at least one of methyl methacrylate-butadiene-styrene copolymer, methyl methacrylate-silicone-acrylate copolymer, ethylene-1-octene copolymer, and ethylene-acrylic acid-glycidyl methacrylate copolymer.
[0065] The toughening agent mentioned above has good thermal stability. When added to polycarbonate composites, it helps to improve their ductility and toughness at high temperatures, reduce the risk of brittle fracture, and thus improve the burn-through resistance of polycarbonate composites.
[0066] In some embodiments, the antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants. Specifically, but not limitingly, the hindered phenolic antioxidant is at least one of antioxidant 1010 and antioxidant 245, and the phosphite antioxidant is at least one of antioxidant 1076 and antioxidant 168.
[0067] The antioxidants mentioned above are commonly used antioxidants. Among them, hindered phenolic antioxidants mainly achieve their antioxidant effect by capturing free radicals. During the oxidation process of materials, free radicals are generated, which can trigger chain reactions, leading to a decline in material performance. Hindered phenolic antioxidants can react with free radicals to generate stable compounds, thereby interrupting the chain reaction of oxidation and protecting the material from oxidative damage. Phosphite antioxidants mainly achieve their antioxidant effect by scavenging peroxides. Phosphite antioxidants can react with peroxides to generate stable compounds, thereby scavenging peroxides, inhibiting the generation of free radicals, and protecting the material from oxidative damage.
[0068] In some embodiments, the lubricant is at least one of silicone powder, pentaerythritol stearate, and stearamide.
[0069] The aforementioned lubricants can reduce the internal and external friction of polycarbonate composites during processing, thereby significantly improving their flowability and resulting in polycarbonate composites with high uniformity. Furthermore, appropriate amounts of lubricant can improve the mechanical properties of polycarbonate composites, reduce their brittleness, and increase their durability. In addition, lubricants such as silicone powder have good electrical insulation properties, which can improve the electrical insulation properties of polycarbonate composites, enabling their wider application in the electronics and electrical appliance fields.
[0070] In another typical embodiment of this application, a method for preparing the polycarbonate composite material of the third aspect of this application is provided, comprising the following steps:
[0071] S1, mix polycarbonate, flame retardant, composite phase change material, toughening agent, antioxidant and lubricant to obtain a mixture;
[0072] S2, the mixture is added to an extruder for melting, extrusion and granulation to obtain a polycarbonate composite material.
[0073] The above preparation method is simple, requires few equipment, and is suitable for industrial application.
[0074] In some embodiments, in S1, mixing is carried out in a high-speed mixer at a mixing rate of 1000 r / min to 2000 r / min. Mixing under these conditions is beneficial for the rapid formation of polycarbonate composite materials.
[0075] In some implementations, in S2, the extruder is a twin-screw extruder.
[0076] In some embodiments, in S2, the process parameters of the extruder are: zone 1 temperature 240℃~245℃, zone 2 temperature 250℃~255℃, zone 3 temperature 260℃~265℃, zone 4 temperature 270℃~275℃, zone 5 temperature 270℃~275℃, zone 6 temperature 270℃~275℃, zone 7 temperature 270℃~275℃, zone 8 temperature 270℃~275℃, zone 9 temperature 275℃~280℃, and die head temperature 285℃~290℃. The speed of the extruder is 300r / min~500r / min.
[0077] The polycarbonate composite material prepared using the above process exhibits low internal stress, good uniformity, and excellent surface quality and mechanical properties. Furthermore, the process requires minimal energy consumption, preventing overheating that could lead to corrosion and wear inside the equipment.
[0078] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.
[0079] Some of the materials used in the embodiments and comparative examples are as follows:
[0080] Porous glass microspheres A: SiO2·P2O5 system porous hollow glass microspheres, melting temperature 550℃, average particle size 50μm, average pore size 1μm, porosity 50%.
[0081] Porous glass microspheres B: SiO2·P2O5 system porous hollow glass microspheres, melting temperature 550℃, average particle size 60μm, average pore size 2μm, porosity 40%.
[0082] Porous glass microspheres C: SiO2·P2O5 system porous hollow glass microspheres, melting temperature 600℃, average particle size 50μm, average pore size 2μm, porosity 30%.
[0083] Porous glass microspheres D: SiO2·P2O5 system porous hollow glass microspheres, melting temperature 400℃, average particle size 200μm, average pore size 10μm, porosity 20%.
[0084] Porous glass microspheres E: SiO2·P2O5 system porous hollow glass microspheres, melting temperature 500℃, average particle size 150μm, average pore size 10μm, porosity 10%.
[0085] Polycarbonate A: The melt flow rate measured at 300℃ and 1.2kg was 8g / 10min, and the number average molecular weight was 30000g / mol.
[0086] Polycarbonate B: The melt flow rate measured at 300℃ and 1.2kg was 15g / 10min, and the number average molecular weight was 26000g / mol.
[0087] Polycarbonate C: The melt flow rate measured at 300℃ and 1.2kg was 20g / 10min, and the number average molecular weight was 24000g / mol.
[0088] Polycarbonate D: The melt flow rate measured at 300℃ and 1.2kg was 30g / 10min, and the number average molecular weight was 13000g / mol.
[0089] methyl methacrylate-silicone-acrylate copolymer: Mitsubishi Rayon, Japan, S2200;
[0090] Example 1
[0091] One embodiment of the composite phase change material of this application, the preparation method of the composite phase change material of this embodiment is as follows:
[0092] S1, 10 parts of nitrate (NaNO3 and KNO3 in a mass ratio of 6:4, with an average particle size of 1μm) were placed in a heating and pressure device. The outer heater heated the interior to 350°C at a heating rate of 20°C / min and then kept it at that temperature. Then, 90 parts of porous glass microspheres A were added to the heating and pressure device to obtain a mixture.
[0093] S2, a composite is obtained by applying a pressure of 400MPa through a heating and pressure device and holding it at 350℃ for 30min;
[0094] S3, the composite is mechanically pulverized and then ball-milled in a ball mill until the particle size is 10μm to obtain powder;
[0095] S4. The powder was washed with a KOH solution with a concentration of 0.1 mol / L and distilled water until the pH of the washing solution was 7. The powder was then filtered to obtain a filter cake, which was dried at 100°C for 24 hours to obtain the composite phase change material.
[0096] Example 2
[0097] One embodiment of the composite phase change material of this application differs from Embodiment 1 only in that, in S1, the weight parts of nitrate are 20 parts and the weight parts of porous glass microspheres A are 80 parts.
[0098] Example 3
[0099] One embodiment of the composite phase change material of this application differs from Embodiment 1 only in that, in S1, the mass ratio of NaNO3 to KNO3 in the nitrate is 5:5, and the average particle size is 1 μm.
[0100] Example 4
[0101] One embodiment of the composite phase change material of this application differs from Embodiment 3 only in that, in S1, the weight parts of nitrate are 20 parts and the weight parts of porous glass microspheres A are 80 parts.
[0102] Example 5
[0103] One embodiment of the composite phase change material of this application differs from Embodiment 1 only in that, in S1, the mass ratio of NaNO3 to KNO3 in the nitrate is 4:6, and the average particle size is 1 μm.
[0104] Example 6
[0105] One embodiment of the composite phase change material of this application differs from Embodiment 1 only in that, in S1, porous glass microspheres B are used instead of porous glass microspheres A.
[0106] Example 7
[0107] One embodiment of the composite phase change material of this application differs from Embodiment 1 only in that, in S1, porous glass microspheres C are used instead of porous glass microspheres A.
[0108] Example 8
[0109] One embodiment of the composite phase change material of this application differs from Embodiment 1 only in that, in S1, porous glass microspheres D are used instead of porous glass microspheres A.
[0110] Example 9
[0111] One embodiment of the composite phase change material of this application differs from Embodiment 1 only in that, in S1, porous glass microspheres E are used instead of porous glass microspheres A.
[0112] Example 10
[0113] One embodiment of the composite phase change material of this application differs from Embodiment 1 only in that, in S2, the pressure is 300 MPa and the temperature is 400 °C.
[0114] Example 11
[0115] One embodiment of the composite phase change material of this application differs from Embodiment 1 only in that, in S2, the pressure is 500 MPa and the temperature is 400 °C.
[0116] Example 12
[0117] This application provides an example of a polycarbonate composite material. This example uses the composite phase change material from Example 1 to prepare the polycarbonate composite material, with the following formulation: 93 parts polycarbonate A, 2 parts composite phase change material, 1 part potassium perfluorobutyl sulfonate, 3 parts methyl methacrylate-organosilicon-acrylate copolymer, 0.5 parts silicone powder, and 0.5 parts antioxidant 1076. The preparation method is as follows:
[0118] S1, add the above ingredients into a high-speed mixer and mix at 1500 rpm to obtain a mixture;
[0119] S2, the mixture is added to a twin-screw extruder for melt extrusion, followed by water-cooled hot-cut granulation to obtain a polycarbonate composite material; the extruder process parameters are: zone 1 temperature 240℃, zone 2 temperature 245℃, zone 3 temperature 250℃, zone 4 temperature 255℃, zone 5 temperature 260℃, zone 6 temperature 265℃, zone 7 temperature 270℃, zone 8 temperature 275℃, zone 9 temperature 275℃, die head temperature 285℃, and twin-screw extruder speed 450rpm.
[0120] Example 13
[0121] This application provides an example of a polycarbonate composite material. This example uses the composite phase change material from Example 1 to prepare the polycarbonate composite material, with the following formulation: 94 parts polycarbonate A, 1 part composite phase change material, 1 part potassium perfluorobutyl sulfonate, 3 parts methyl methacrylate-silicone-acrylate copolymer, 0.5 parts silicone powder, and 0.5 parts antioxidant 1076. The preparation method is as follows:
[0122] S1, add the above ingredients into a high-speed mixer and mix at 1500 rpm to obtain a mixture;
[0123] S2, the mixture is added to a twin-screw extruder for melt extrusion, followed by water-cooled hot-cut granulation to obtain a polycarbonate composite material; the extruder process parameters are: zone 1 temperature 243℃, zone 2 temperature 248℃, zone 3 temperature 253℃, zone 4 temperature 259℃, zone 5 temperature 264℃, zone 6 temperature 267℃, zone 7 temperature 273℃, zone 8 temperature 278℃, zone 9 temperature 279℃, die head temperature 287℃, and twin-screw extruder speed 450rpm.
[0124] Example 14
[0125] This application provides an example of a polycarbonate composite material. This example uses the composite phase change material from Example 2, and its formulation is as follows: 93 parts polycarbonate A, 2 parts composite phase change material, 1 part potassium perfluorobutyl sulfonate, 3 parts methyl methacrylate-silicone-acrylate copolymer, 0.5 parts silicone powder, and 0.5 parts antioxidant 1076. The preparation method is as follows:
[0126] S1, add the above ingredients into a high-speed mixer and mix at 1500 rpm to obtain a mixture;
[0127] S2, the mixture is added to a twin-screw extruder for melt extrusion, followed by water-cooled hot-cut granulation to obtain a polycarbonate composite material; the extruder process parameters are: zone 1 temperature 240℃, zone 2 temperature 245℃, zone 3 temperature 250℃, zone 4 temperature 255℃, zone 5 temperature 260℃, zone 6 temperature 265℃, zone 7 temperature 270℃, zone 8 temperature 275℃, zone 9 temperature 275℃, die head temperature 285℃, and twin-screw extruder speed 450rpm.
[0128] Example 15
[0129] This application provides an example of a polycarbonate composite material. This example uses the composite phase change material from Example 2, and its formulation is as follows: 94 parts polycarbonate A, 1 part composite phase change material, 1 part potassium perfluorobutyl sulfonate, 3 parts methyl methacrylate-silicone-acrylate copolymer, 0.5 parts silicone powder, and 0.5 parts antioxidant 1076. The preparation method is as follows:
[0130] S1, add the above ingredients into a high-speed mixer and mix at 1500 rpm to obtain a mixture;
[0131] S2, the mixture is added to a twin-screw extruder for melt extrusion, followed by water-cooled hot-cut granulation to obtain a polycarbonate composite material; the extruder process parameters are: zone 1 temperature 240℃, zone 2 temperature 245℃, zone 3 temperature 250℃, zone 4 temperature 255℃, zone 5 temperature 260℃, zone 6 temperature 265℃, zone 7 temperature 270℃, zone 8 temperature 275℃, zone 9 temperature 275℃, die head temperature 285℃, and twin-screw extruder speed 450rpm.
[0132] Example 16
[0133] One embodiment of the polycarbonate composite material of this application is a polycarbonate composite material prepared using the composite phase change material in Example 3. The formulation is as follows: 93 parts polycarbonate A, 2 parts composite phase change material, 1 part potassium perfluorobutyl sulfonate, 3 parts methyl methacrylate-organosilicon-acrylate copolymer, 0.5 parts silicone powder, and 0.5 parts antioxidant 1076. The preparation method is as follows:
[0134] S1, add the above ingredients into a high-speed mixer and mix at 1500 rpm to obtain a mixture;
[0135] S2, the mixture is added to a twin-screw extruder for melt extrusion, followed by water-cooled hot-cut granulation to obtain a polycarbonate composite material; the extruder process parameters are: zone 1 temperature 240℃, zone 2 temperature 245℃, zone 3 temperature 250℃, zone 4 temperature 255℃, zone 5 temperature 260℃, zone 6 temperature 265℃, zone 7 temperature 270℃, zone 8 temperature 275℃, zone 9 temperature 275℃, die head temperature 285℃, and twin-screw extruder speed 450rpm.
[0136] Example 17
[0137] One embodiment of the polycarbonate composite material of this application is a polycarbonate composite material prepared using the composite phase change material in Example 3. The formulation is as follows: 94 parts polycarbonate A, 1 part composite phase change material, 1 part potassium perfluorobutyl sulfonate, 3 parts methyl methacrylate-organosilicon-acrylate copolymer, 0.5 parts silicone powder, and 0.5 parts antioxidant 1076. The preparation method is as follows:
[0138] S1, add the above ingredients into a high-speed mixer and mix at 1500 rpm to obtain a mixture;
[0139] S2, the mixture is added to a twin-screw extruder for melt extrusion, followed by water-cooled hot-cut granulation to obtain a polycarbonate composite material; the extruder process parameters are: zone 1 temperature 240℃, zone 2 temperature 245℃, zone 3 temperature 250℃, zone 4 temperature 255℃, zone 5 temperature 260℃, zone 6 temperature 265℃, zone 7 temperature 270℃, zone 8 temperature 275℃, zone 9 temperature 275℃, die head temperature 285℃, and twin-screw extruder speed 450rpm.
[0140] Example 18
[0141] One embodiment of the polycarbonate composite material of this application is a polycarbonate composite material prepared using the composite phase change material in Example 4. The formulation is as follows: 93 parts polycarbonate A, 2 parts composite phase change material, 1 part potassium perfluorobutyl sulfonate, 3 parts methyl methacrylate-organosilicon-acrylate copolymer, 0.5 parts silicone powder, and 0.5 parts antioxidant 1076. The preparation method is as follows:
[0142] S1, add the above ingredients into a high-speed mixer and mix at 1500 rpm to obtain a mixture;
[0143] S2, the mixture is added to a twin-screw extruder for melt extrusion, followed by water-cooled hot-cut granulation to obtain a polycarbonate composite material; the extruder process parameters are: zone 1 temperature 240℃, zone 2 temperature 245℃, zone 3 temperature 250℃, zone 4 temperature 255℃, zone 5 temperature 260℃, zone 6 temperature 265℃, zone 7 temperature 270℃, zone 8 temperature 275℃, zone 9 temperature 275℃, die head temperature 285℃, and twin-screw extruder speed 450rpm.
[0144] Example 19
[0145] One embodiment of the polycarbonate composite material of this application is a polycarbonate composite material prepared using the composite phase change material in Example 4. The formulation is as follows: 94 parts polycarbonate A, 1 part composite phase change material, 1 part potassium perfluorobutyl sulfonate, 3 parts methyl methacrylate-organosilicon-acrylate copolymer, 0.5 parts silicone powder, and 0.5 parts antioxidant 1076. The preparation method is as follows:
[0146] S1, add the above ingredients into a high-speed mixer and mix at 1500 rpm to obtain a mixture;
[0147] S2, the mixture is added to a twin-screw extruder for melt extrusion, followed by water-cooled hot-cut granulation to obtain a polycarbonate composite material; the extruder process parameters are: zone 1 temperature 240℃, zone 2 temperature 245℃, zone 3 temperature 250℃, zone 4 temperature 255℃, zone 5 temperature 260℃, zone 6 temperature 265℃, zone 7 temperature 270℃, zone 8 temperature 275℃, zone 9 temperature 275℃, die head temperature 285℃, and twin-screw extruder speed 450rpm.
[0148] Examples 20-26
[0149] Examples of polycarbonate composite materials in this application, Examples 20 to 26 are polycarbonate composite materials prepared using the composite phase change materials in Examples 5 to 11, and their formulations are as follows: 93 parts polycarbonate A, 2 parts composite phase change material, 1 part potassium perfluorobutyl sulfonate, 3 parts methyl methacrylate-organosilicon-acrylate copolymer, 0.5 parts silicone powder, and 0.5 parts antioxidant 1076; the preparation method is the same as in Example 12.
[0150] Examples 27-29
[0151] The polycarbonate composite material examples of this application, Examples 27 to 29, differ from Example 12 only in the type of polycarbonate. In Example 27, polycarbonate B is used instead of polycarbonate A; in Example 28, polycarbonate C is used instead of polycarbonate A; and in Example 29, polycarbonate D is used instead of polycarbonate A.
[0152] Example 30
[0153] The polycarbonate composite material of this application differs from Example 12 only in that the type of flame retardant is different, with bromine-based carbonate oligomer (Dahu, BC-58) replacing potassium perfluorobutyl sulfonate.
[0154] Comparative Example 1
[0155] The polycarbonate composite material of this application differs from Example 12 only in that the type of composite phase change material is different. The composite phase change material differs from Example 1 only in that in S1, the temperature was not raised to 350°C and the mixture was obtained at room temperature. S2 is omitted.
[0156] Comparative Example 2
[0157] The embodiment of the polycarbonate composite material of this application differs from that of Example 12 only in that no composite phase change material is added.
[0158] Performance testing
[0159] The polycarbonate composite materials of Examples 12-30 and Comparative Examples 1-2 were injection molded into strips or templates for performance testing. The test methods are as follows, and the test results are shown in Table 1.
[0160] (1) Notched impact strength of cantilever beam (kJ / m) 2 Tested according to GB / T 1843-2008, the test condition is 23℃;
[0161] (2) Needle flame test: The test shall be conducted in accordance with GB / T 4943.1-2022;
[0162] (3) Vertical burning: Tested according to UL94.
[0163] Table 1
[0164]
[0165]
[0166] The test results above show that the polycarbonate composite material prepared with the composite phase change material of this application has good flame retardant properties, and its burn-through time in the needle flame test is all above 85s, indicating good burn-through resistance. Meanwhile, its cantilever beam notched impact strength is all above 40kJ / cm². 2 Suitable for use as a fireproof enclosure for a variety of equipment.
[0167] In Comparative Example 1, when a composite phase change material was prepared at room temperature, it was difficult for salt to enter the pores of the porous glass microspheres. As a result, under high temperature conditions, the structure of the composite phase change material in the polycarbonate composite material was prone to collapse, and the salt was easily leaked out and lost, making it difficult to improve the burn-through resistance of the polycarbonate composite material.
[0168] The polycarbonate composite material described in Comparative Example 2 does not contain composite phase change material, and its burn-through resistance is significantly worse than that of the Example.
[0169] In addition, the performance test results of comparative examples 20-24 show that when the average particle size of the porous glass microspheres is 50μm-100μm, the melting temperature is 550℃-650℃, the average pore size is 1μm-5μm, and the porosity is 20%-50%, the burn-through time of the polycarbonate composite material is higher than 100s, exhibiting excellent burn-through resistance and making it suitable for applications in multiple fields.
[0170] Comparing the test results of Examples 27-29, it can be found that the polycarbonate melt with a melt index of 30 g / 10 min has poor melt strength and poor burn-through resistance. Furthermore, the experiment showed that polycarbonate with a melt index below 8 g / 10 min has poor processing performance. The above results indicate that composite materials prepared with polycarbonate melt indices of 8-20 g / 10 min and number-average molecular weights of 24000-30000 g / mol all exhibit burn-through resistance exceeding 100 s and cantilever beam notched impact strength exceeding 40 kJ / cm. 2 It is more suitable for the current trend of thin-walled development.
[0171] Comparing the test results of Example 12 and Example 30, it can be found that potassium perfluorobutyl sulfonate has a higher flame retardant efficiency than bromine carbonate oligomers at the same flame retardant content.
[0172] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A composite phase change material, characterized in that, It includes porous glass microspheres and salt, with at least a portion of the salt located within the pores of the porous glass microspheres; the mass ratio of the porous glass microspheres to the salt is (80-90):(10-20); the salt forms molten salt after melting.
2. The composite phase change material according to claim 1, characterized in that, The salt comprises sodium nitrate and potassium nitrate, and the mass ratio of sodium nitrate to potassium nitrate in the salt is (4-6):(4-6).
3. The composite phase change material according to claim 1 or 2, characterized in that, Includes at least one of the following features: (1) The average particle size of the salt is 1 μm to 5 μm; (2) The average particle size of the porous glass microspheres is 50 μm to 100 μm; (3) The melting temperature of the porous glass microspheres is 550℃~650℃; (4) The average pore size of the porous glass microspheres is 1μm to 5μm; (5) The porosity of the porous glass microspheres is 20% to 50%; (6) The melting point of the salt is 350℃~400℃.
4. A method for preparing a composite phase change material, characterized in that, Includes the following steps: S1, heat the salt to 350℃~400℃, then add porous glass microspheres to obtain a mixture; S2, the mixture is subjected to heat preservation and pressure treatment at 300MPa~500MPa and 350℃~400℃ to obtain the composite phase change material; The mass ratio of the porous glass microspheres to the salt is (80-90):(10-20), and the salt melts to form molten salt.
5. The method for preparing the composite phase change material according to claim 4, characterized in that, Includes at least one of the following features: (1) The salt comprises sodium nitrate and potassium nitrate, and the mass ratio of sodium nitrate to potassium nitrate is (4-6): (4~6); (2) In S2, after the heat preservation and pressure treatment, the process also includes grinding, cleaning and drying; after drying, the composite phase change material is obtained.
6. A polycarbonate composite material, characterized in that, The composition comprises the following components in parts by weight: 89-94.7 parts polycarbonate, 0.5-1.5 parts flame retardant, 1-2 parts composite phase change material, 3-5 parts toughening agent, 0.2-2 parts antioxidant, and 0.1-1 parts lubricant; wherein the composite phase change material is the composite phase change material according to any one of claims 1 to 3, or the composite phase change material prepared by the preparation method of claim 4 or 5.
7. The polycarbonate composite material according to claim 6, characterized in that, Includes at least one of the following features: (1) The melt flow rate of the polycarbonate measured at 300℃ and 1.2kg is 8g / 10min to 20g / 10min; (2) The number average molecular weight of the polycarbonate is 24,000 g / mol to 30,000 g / mol.
8. The polycarbonate composite material according to claim 6, characterized in that, Includes at least one of the following features: (1) The flame retardant is a sulfonate flame retardant; (2) The toughening agent is at least one of methyl methacrylate-butadiene-styrene copolymer, methyl methacrylate-organosilicon-acrylate copolymer, ethylene-1-octene copolymer, and ethylene-acrylic acid-glycidyl methacrylate copolymer; (3) The antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants; (4) The lubricant is at least one of silicone powder, pentaerythritol stearate, and stearamide.
9. A method for preparing a polycarbonate composite material according to any one of claims 6 to 8, characterized in that, Includes the following steps: S1, mix polycarbonate, flame retardant, composite phase change material, toughening agent, antioxidant and lubricant to obtain a mixture; S2, the mixture is added to an extruder for melting, extrusion, and granulation to obtain the polycarbonate composite material.
10. The preparation method according to claim 9, characterized in that, Includes at least one of the following features: (1) In S1, the mixing is carried out in a high-speed mixer; (2) In S2, the extruder is a twin-screw extruder; (3) In S2, the process parameters of the extruder are: Zone 1 temperature 240℃~245℃, Zone 2 temperature 245℃~250℃, Zone 3 temperature 250℃~255℃, Zone 4 temperature 255℃~260℃, Zone 5 temperature 260℃~265℃, Zone 6 temperature 265℃~270℃, Zone 7 temperature 270℃~275℃, Zone 8 temperature 270℃~280℃, Zone 9 temperature 275℃~280℃, Die head temperature 285℃~290℃, and the speed of the extruder is 300r / min~500r / min.
